Chiari 1 Malformation Presenting as Central Sleep Apnea during Pregnancy: A Case Report, Treatment Considerations, and Review of the Literature - St. Louis, Erik K.; Jinnur, Praveen; McCarter, Stuart J.; Duwell, Ethan J.; Benarroch, Eduardo E.; Kantarci, Kejal; Pichelmann, Mark A.; Silber, Michael H.; Boeve, Bradley F.; Olson, Eric J.; Morgenthaler, Timothy I.; Somers, Virend K. (Frontiers in Neurology, 2014)
Purpose: Chiari malformation (CM) type-1 frequently causes obstructive or central sleep-disordered breathing (SDB) in both adults and children, although SDB is relatively rare as a presenting manifestation in the absence of other neurological symptoms. The definitive treatment of symptomatic CM is surgical decompression. We report a case that is, to our knowledge, a novel manifestation of central sleep apnea (CSA) due to CM type-1 with severe exacerbation and initial clinical presentation during pregnancy. Methods: Case report from tertiary care comprehensive sleep medicine center with literature review of SDB manifestations associated with CM type-1. PubMed search was conducted between January 1982 and October 2013. Results: We report a 25-year-old woman with severe CSA initially presenting during her first pregnancy that eventually proved to be caused by CM type-1. The patient was successfully treated preoperatively by adaptive servoventilation (ASV), with effective resolution of SDB following surgical decompression, and without recurrence in a subsequent pregnancy. Our literature review found that 58% of CM patients with SDB had OSA alone, 28% had CSA alone, 8 (10%) had mixed OSA/CSA, and 6 (8%) had hypoventilation. Of CM patients presenting with SDB, 50% had OSA, 42% had CSA, 8% had mixed OSA/CSA, and 10.4% had hypoventilation. We speculate that CSA may develop in CM patients in whom brainstem compression results in excessive central chemoreflex sensitivity with consequent hypocapnic CSA. Conclusion: Chiari malformation type-1 may present with a diversity of SDB manifestations, and timely recognition and surgical referral are necessary to prevent further neurological deficits. ASV therapy can effectively manage CSA caused by CM type-1, which may initially present during pregnancy.